Snow sports-specific extension of the IOC consensus statement: methods for recording and reporting epidemiological data on injury and illness in sports - Spörri, J.; McGawley, K.; Alhammoud, M.; Bahr, R.; Dios, C.; Engebretsen, L.; Gilgien, M.; Gouttebarge, V.; Hanstock, H.; Haugvad, L.; Hörterer, H.; Kastner, T.; et al. (British Journal of Sports Medicine, 2025)
The International Olympic Committee`s (IOC) consensus statement on `methods for recording and reporting of epidemiological data on injury and illness in sport` recommended standardising methods to advance data collection and reporting consistency. However, additional aspects need to be considered when these methods are applied to specific sports settings. Therefore, we have developed a snow sports-specific extension of the IOC statement to promote the harmonisation of injury and illness registration methods among athletes of all levels and categories in the different disciplines governed by the International Ski and Snowboard Federation (FIS), which is also applicable to other related snow sports such as biathlon, ski mountaineering, and to some extent, para snow sports. The panel was selected with the aim of representing as many different areas of expertise/backgrounds, perspectives and diversity as possible, and all members were assigned to thematic subgroups based on their profiles. After panel formation, all members were provided with an initial draft of this extension, which was used as a basis for discussion of aspects specific to the discipline, application context, level and sex within their snow sports subgroup topic. The outcomes were then aligned with the IOC`s existing consensus recommendations and incorporated into a preliminary manuscript draft. The final version of this snow sports-specific extension was developed and approved in two iterative rounds of manuscript revisions by all consensus panel members and a final meeting to clarify open discussion points. This snow sports-specific extension of the IOC statement is intended to guide researchers, international and national sports governing bodies, and other entities recording and reporting epidemiological data in snow sports to help standardise data from different sources for comparison and future research.